Navigating Interoperability, Security, and Scalability: A Narrative Review of IoT Architectures in Smart Cities - Nasihien, Ronny Durrotun; Juwari (Indonesian Scientific Publication, 2024)
The rapid advancement of Internet of Things (IoT) technologies has driven the transformation of urban centers into smart cities, yet significant challenges remain in the implementation of interoperable, secure, and scalable IoT architectures. This narrative review aims to explore the primary issues and proposed solutions related to interoperability, cybersecurity, and infrastructure scalability in IoT-based smart city frameworks. Literature was gathered from leading databases including Scopus, Web of Science, and IEEE Xplore, using Boolean search strategies with keywords such as